2005
DOI: 10.1163/156853805774806205
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of the water snake Helicops infrataeniatus (Colubridae) in southern Brazil

Abstract: The reproductive cycle, sexual maturity, fecundity, and sexual dimorphism of Helicops infrataeniatus Jan, 1865, were inferred from the analysis of 374 preserved specimens (110 males, 140 females) from the eastern Central Depression of Rio Grande do Sul, Brazil. There was no statistical difference between the SVL of newborn males and females, but mature females attained greater length than mature males. The tail of mature individuals was proportionally longer in males than in females. Males matured at a smaller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
11
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 8 publications
7
11
0
7
Order By: Relevance
“…On the contrary, Middle Paraná River reptiles were strongly influenced by the marked seasonality in temperature and precipitations, and their activity and reproductive patterns were coincident with the warmest and rainiest months of the year. This seasonal pattern coincides with what was indicated for other reptiles in subtropical and temperate regions of South America (e.g., southern Brazil, Schmid de Aguiar and Di-Bernardo 2005). Particular adjustments were observed in the reproductive types and phenology when species of aquatic and terrestrial snakes were compared.…”
Section: Influence Of Flood Pulses and Other Environmental Factors Onsupporting
confidence: 86%
See 2 more Smart Citations
“…On the contrary, Middle Paraná River reptiles were strongly influenced by the marked seasonality in temperature and precipitations, and their activity and reproductive patterns were coincident with the warmest and rainiest months of the year. This seasonal pattern coincides with what was indicated for other reptiles in subtropical and temperate regions of South America (e.g., southern Brazil, Schmid de Aguiar and Di-Bernardo 2005). Particular adjustments were observed in the reproductive types and phenology when species of aquatic and terrestrial snakes were compared.…”
Section: Influence Of Flood Pulses and Other Environmental Factors Onsupporting
confidence: 86%
“…It is probable that newborns and gravid females of this aquatic snake could find a higher availability of aquatic environments in floodplain lakes and marshes, optimizing the possibilities to find refuge and feeding areas. Reproduction of H. leopardinus is similar to that of H. infrataeniatus, whose reproductive cycle extends even until June in southern Brazil (Aguiar and Di-Bernardo 2005). We observed that oviposition of the aquatic turtle Phrynops hilarii in the Middle Paraná River is concentrated in March (six nests registered, a turtle digging the nest, a run-over turtle with 13 well-developed eggs in its body) and April (three nests recorded), also coinciding with the maximum historical river levels.…”
Section: Reproductive Strategiessupporting
confidence: 51%
See 1 more Smart Citation
“…The difference between the number of vitellogenic follicles and eggs found in the oviduct was not significant (Mann-Whitney test, U = 19.0, Z = 0.3917, p = 0.6953, n = 16), suggesting that the clutches can be regarded The pattern found for E. cyanopleura in relation to the size of the tail (there was no significant difference between males and females) does not correspond to the general pattern found in snakes, in which males have longer tails than females (KING 1989, SHINE 1993, BALESTRIN & DI-BERNARDO 2005, AGUIAR & DI-BERNARDO 2005. Body size is a major determinant of the type of prey that a species can exploit (CADLE & GREENE 1993) and the absence of dimorphism in the tail may be related to ecological factors, such as foraging strategy and defense mechanisms.…”
Section: Resultsmentioning
confidence: 89%
“…A maioria dos gimnoftalmídeos possui uma ampla estação reprodutiva (Vitt 1982), por exemplo, fêmeas de Cercosaura ocellata, no Peru, estão ovígeras durante seis meses do ano (setembro a fevereiro) (Dixon & Soini 1986). Contudo, o clima Mesotérmico temperado da região sul do Brasil parece impor restrições fisiológicas que limitam a atividade de diversas espécies de répteis (Maciel et al 2004, Hartmann et al 2004, Aguiar & Di-Bernardo 2005, Balestrin & Di-Bernardo 2005, Cappellari 2005) aos meses quentes do ano. Assim, muito do que é sabido para répteis de regiões tropicais do Brasil pode não ser útil para as populações ou espécies proximamente relacionadas no sul do Brasil (Di-Bernardo et al 2007).…”
Section: Ciclo Reprodutivounclassified